Person-organization fit and innovative work behavior: The mediating role of perceived organizational support, affective commitment and trust - Muhammad Waheed Akhtar; Fauzia Syed; Mudassir Husnain; Saima Naseer (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
The present study investigates the mediating role of perceived organizational support, trust and affective commitment in the relationship between person-organization fit and innovative work behavior. Sample consists of 151 respondents. Existing validated questionnaires were used for the collection of data from nurses employed in different hospitals of Islamabad, Pakistan. PROCESS Macros technique is applied to test the hypothesized model. The results show that affective commitment, perceived organizational support, and trust have an indirect effect on the relationship between person-organization fit and innovative work behavior. Managerial implications, directions and limitations for the future studies are mentioned at the end.
Keywords: 330; perceived organizational support; person-organization fit; affective commitment; innovative work behavior; trust; nurses; hospitals